EFFECTIVENESS OF INDIVIDUAL COUNSELING SERVICES IN STUDENTS' SOCIAL DECISION MAKING SKILLS - Pratiwi Damanik, Aulia; Yolanda, Yuke (BRIGHT VISION Journal of Language and Education, 2023)
Improving students' decision-making skills using a qualitative approach with the library research method which is carried out using literature in the form of books, notes or other literature as the main object. The purpose of making this journal is to provide assistance to students using individual counseling services to be brave in making decisions for themselves. Decision making skills are the ability to control oneself so as not to be easily influenced by social stimuli. Many students do not dare to make decisions for themselves due to internal and external factors.